2020
DOI: 10.1186/s43055-020-00170-w
|View full text |Cite
|
Sign up to set email alerts
|

Can PET/CT detect recurrence in post-operative colorectal carcinoma patients with elevated CEA level?

Abstract: Background: PET is considered to be the most sensitive and specific modality for the detection of recurrent colorectal cancer. This study is to assess the role of F18-FDG PET/CT in post-operative assessment in a patient with colorectal cancer with elevated CEA level to rule out local recurrence and/or metastasis and hence guiding the clinician to the proper management strategy. Results: This study was performed on 45 patients who underwent surgical resection of the colon and/or rectal cancer; they were referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…However, several authors reported FDG PET/CT as highy sensitive in the detection of liver metastases in patients with CRC [71,72]. If compared to CECT, FDG PET/CT is superior, in particular for the detection of occult metastases [40,42]. Results obtained in a study of Cinar et al are in line with previous reports.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, several authors reported FDG PET/CT as highy sensitive in the detection of liver metastases in patients with CRC [71,72]. If compared to CECT, FDG PET/CT is superior, in particular for the detection of occult metastases [40,42]. Results obtained in a study of Cinar et al are in line with previous reports.…”
Section: Discussionsupporting
confidence: 75%
“…Ragheb et al performed FDG PET/CT on 45 CRC patients with elevated CEA levels during the postoperative surveillance. Compared to previous authors, they obtained similar sensitivity, specificity, PPV, and NPV of 96.9%, 83.3%, 94.2%, and 90%, respectively [40]. In addition, Gade et al reported a high diagnostic performance of FDG PET/CT in recurrent CRC obtained on 73 patients with rising CEA levels.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, PET/CT is also reported as a highly sensitive method in diagnostics of liver metastatic disease [ 73 , 74 ]. In comparison to CT, PET/CT is a superior diagnostic method, particularly in detecting occult metastases [ 38 , 48 ]. Results obtained in a study by Cinar et al align with previous reports.…”
Section: Discussionmentioning
confidence: 99%